John Glenn : a memoir - Glenn, John (New York Bantan Books, 2000)
The first American astronaut to orbit the globe recalls a life testing the limits, from his days as a daredevil test pilot, to his terms in the U.S. Senate, to his most recent flight into space aboard the shuttle Discovery
d unk
Keywords: Astronauts -- Biography -- United States; Legislators -- Biography -- United States